PARADIGMA STRUCTURE CONDUCT AND PERFORMANCE VERSUS HIPOTESIS EFISIENSI: MANAKAH YANG MENCERMINKAN INDUSTRI PERBANKAN INDONESIA? - Pracoyo Budi Jatmiko (Faculty of Economics and Business, Universitas Gadjah Mada, 2000)
There are two competing hyphotesis with regard to market structure and performance. The first hypothesis is structure-conduct-performance paradigm which emphasized on market collusion and the second hypothesis is efficiency hyphotesis which emphasized on market efficiency. Both hypothesis are mutually exclusive. This article conducted test for both hyphotesis with respect to the Indonesian banking industry using pooling data from 16 largest bank for period 1988-1995. The results were suprisingly support the efficiency hyphotesis. It means that government regulation has succesfully fostered banks to enhance their efficiency and then improved their profit. However, readers have to use the finding prudently because there is a few sample limitation.